Akibat Hukum Adat Semenda dalam Sistem Pewarisan Suku Talang Mamak ditinjau dari Hukum Keperdataan di Indonesia - Rr. Chantika Vebyola Wijaya; Dedo Indra Pratama; Adib Yanuar Gunawan; Wiwin Yulianingsih (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The inheritance law itself is part of the civil law and the smallest part of the family law. The customary law inheritance system includes 3 (three) patterns, namely patrilineal, matrilineal, and parental. One of the tribes that still applies customary inheritance law is the Talang Mamak Tribe. This research explores the application of the inheritance of the Talang Mamak Tribe in the customary inheritance system in Indonesia and its legal consequences in terms of aspects of Indonesian civil law. This research is of a normative juridical type using a statutory debate approach and a concept approach. The secondary data used comes from literature studies with analytical descriptive analytical methods. The result of the research obtained by Penilis is that most of the Talang Mamak people are known to have converted to Islam. The traditional inheritance of the Talang Mamak Tribe basically uses a matrilineal system, where the heirs are daughters. The role of Ninik amak and the daughter here is to be the ruler or controller of the inheritance and the custodian of all the brothers of the wife including the sons. According to Article 105 and Article 109 of the Civil Code, this is inversely proportional to the position of women who are classified as legally incompetent. The inheritance system in the Talang Mamak Tribe should be given legal protection by the government specifically. Keywords: , , ,